Causal relationships between air pollution and common autoimmune diseases: a two-sample Mendelian randomization study - Ming Zhang; Yidian Wang; Shouye Hu; Yue Wu (Scientific Reports)
Abstract Air pollution is strongly associated with autoimmune diseases (ADs), however, the genetic causality between them remains poorly understood. Therefore, the aim of this study is to determine the relationship between common air pollutants and ADs through Mendelian randomization (MR) analysis. We conducted a MR study using aggregated data from publicly available genome-wide association studies (GWAS). Single nucleotide polymorphisms (SNPs) associated with 5 common air pollutants are used as instrumental variables. Random-effects inverse variance weighted (IVW) is used as the primary method to assess causal relationships, with results reported in terms of odds ratios (OR). In addition, we used a two-step MR to assess the mediating role of common risk factors for ADs in the effects of air pollution on ADs. Our analysis revealed causal associations between selected air pollutants and specific ADs. Exposure to nitrogen oxides was positively associated with the risk of rheumatoid arthritis (RA) (OR = 1.47,95% CI 1.01–2.14, P = 0.043), Sjogren’s syndrome (SS) (OR = 2.29,95% CI 1.08–4.89, P = 0.032), and systemic lupus erythematosus (OR = 7.26,95% CI 2.25–23.40, P = 9.10E−04). Genetically predicted PM2.5 and PM10 were risk factors for ulcerative colitis (OR = 1.68,95% CI 1.05–2.68, P = 0.032) and psoriasis (OR = 1.34,95% CI 1.02–1.76, P = 0.037), respectively. Our results also suggest a negative causal relationship between PM2.5–10 and SS (OR = 0.29, 95% CI 0.10–0.90, P = 0.032). In risk factor-related mediation analyses, BMI and smoking mediated 6% (95% CI 1–10%) and 9% (95% CI 2–17%) of the effect of nitrogen oxides on RA, respectively. This study provides evidence of a causal relationship between air pollutants and specific ADs risks, suggesting that improving air pollution may be important in preventing ADs.